“Cultural Code” of a Virtual Personality: Social Safety in the Digital Age - Andrey V. Ivanov; Vadim E. Kozlov; Rishat A. Guzeirov (RUDN Journal of Philosophy, 2025)
Authors base their study upon research materials of the gamer communities, analyze the risks of deconstruction of ethnic, religious and gender identity for modern Russian society. The phenomenon of virtual identity is considered as a part of philosophical - anthropological paradigm, taking into account the current social context and possible prospects. Using the methodological principles of E. Husserl’s phenomenological reduction, as well as P. Berger and T. Luckmann’s social constructionalism, and P. Bourdieu’s theory of social field they describe the mechanisms of construction of social reality by representatives of the community of gamers, who act as agents of habitualization of a new type of social space - virtual reality. After analyzing the typical frameworks of interpersonal and intragroup interaction in the form of interviews, the authors came to the conclusion that “traditional” types of self-identification through attribution with an ethnic or religious group lose in the studied environment not only their relevance, but also the function of maintaining the “I-structure”. At the same time, the ontology of the game often actualizes virtual masculinity in a hypertrophied form, which can hide its compensatory nature. Thus, the phenomenon of virtual personality is becoming more and more widespread and “real”. The gamer community in this case is just one of the most striking examples of such social transformations. At the same time, the extinction of traditional identities combined with the internalization of latent narratives, embedded in the plots of most games by their developers increase the risks of erosion of such a complex socio-cultural space as modern Russian society.